Gene therapy for neovascular age-related macular degeneration: rationale, clinical trials and future directions. Issue 2 (8th April 2020) - Guimaraes, Thales Antonio Cabral de; Georgiou, Michalis; Bainbridge, James W B; Michaelides, Michel
Abstract : Age-related macular degeneration (AMD) is one of the leading causes of irreversible blindness in the developed world. Antivascular endothelial growth factor therapy has transformed the management and outcome of neovascular AMD (nAMD), although the need for repeated intravitreal injections—even lifelong—and the related complications, high drug costs, frequent clinic visits and repeated imaging have resulted in an enormous burden both to healthcare systems and patients. The application of gene therapy approaches for sustained delivery of a range of antiangiogenic proteins has the promise of helping to address these aforementioned challenges. A number of early phase clinical trials of gene therapy in nAMD have provided encouraging results, with many more ongoing or anticipated. There remain significant areas of controversy, including regarding the optimal treatment targets, routes of administration and potential safety concerns. In this review we aim to provide an update of the current status of gene therapy for nAMD and briefly discuss future prospects.